THE CALCULATION OF THE BUILDING STRUCTURE OF INSTITUT TEKNOLOGI DAN BISNIS SABDA SETIA KOTA PONTIANAK - Rahmanto, Fiqih; Elvira, Elvira; Supriyadi, Asep (Fakultas Teknik Universitas Tanjungpura, 2023)
The publishing of the new Indonesian seismic code SNI-1729-2019, which was just issued at the end of 2017, is one example of how laws controlling building construction have been changed to keep up with the times, which is the earth study result by Pusat Studi Gempa Nasional (PUSGEN) update includes incorporating a new source of an earthquake, new active faults, more accurate topography map, and earthquake catalog. One of the new seismic zones in the SNI is Pontianak, so in planning buildings in Pontianak, earthquake force parameters must be calculated so that in the event of an earthquake, anticipatory measures can be taken so as not to cause significant losses. This study is planning the structure of Institut Teknologi dan Bisnis Sabda Setia Kota Pontianak building, which refers to the Indonesian seismic code SNI-1729-2019. The structural analysis is carried out using the help of a structural analysis program adjusted to the value of the planned structural dimensions, which are floor slabs with a thickness of 100 mm, main beams 350/700 mm, child beams 300/600 mm and 250/500 mm, to columns K1 D-800 mm and K2 500Ã—500 mm.